Self Financed Technical University - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 1993)
It was UGC which strongly advocated the establishment of protessional universities in seventies, but some how this suggestion did not get the attention it deserved. Even today, we have only a few Technological Universities whereas quite a few professional Universities have been set up in other professions like Medicine, Agriculture, Ayurved, Veterinary etc.